The Influence of Social Media Marketing and Cash on Delivery on Purchase Decisions at Don's Bakery Gorontalo - Suleman, Siti Samsia; Taan, Hapsawati; Ismail, Yulinda L (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study aims to determine the effect of Social Media Marketing and Cash on Delivery on purchasing decisions at Don's Bakery Gorontalo. This study uses a quantitative approach with a purposive sampling technique with a total of 96 respondents. Data collection was carried out through questionnaires and analyzed using multiple linear regression analysis with the help of SPSS. The results of the study indicate that, partially, Social Media Marketing has a positive and significant effect on purchasing decisions. Likewise, Cash on Delivery also has a positive and significant effect on purchasing decisions. Simultaneously, both variables together influence the increase in consumer purchasing decisions. Based on the results of the study, marketing strategies through social media and the convenience of the payment system through Cash on Delivery have proven effective in encouraging consumers to make purchases at Don's Bakery. This finding emphasizes the importance of utilizing social media and practical payment methods in shaping consumer purchasing decisions.